A Special Antipyroplasmosis Prophylactic Agent Derived from The Piroplasma Begiminum Uz Strain in Cattle with Large Horns - Baratov Jahongir Nurmuhammadiyevich; Goyipova Mutabar Ergashevna; Xo‘jaxonov Shohruz Idricxo‘ja o‘gli; Komolov Fayzulla Burxon o‘g‘li (Zien Journals, 2023)
A method has been developed for the production of a radiovaccine against piroplasmosis in cattle. When studying the reactogenic properties, a weak virulence of the vaccine material irradiated at a dose of 35 krad was revealed, and the preservation of immunogenicity up to 6 months after immunization was noted
Keywords: pyroplasmosis; immunogenicity; cattle, 35 krad